2-Methylimidazole-assisted synthesis of a two-dimensional MOF-5 catalyst with enhanced catalytic activity for the Knoevenagel condensation reaction. Issue 36 (6th September 2018) - Guo, Changyan; Zhang, Yonghong; Zhang, Li; Zhang, Yi; Wang, Jide
Abstract : A novel and facile strategy was developed for the synthesis of a 2D MOF-5 catalyst with 2-methyimidazole as regulation reagent and a Lewis basic site, which showed excellent catalytic activity in Knoevenagel condensation. Abstract : We report a facile strategy to fabricate two-dimensional (2D) MOF-5 with a thickness of 4 nm with 2-methylimidazole (2-MI) as a coordination regulator. 2-MI can inhibit the growth of MOF-5 in the vertical direction by competitive coordination to obtain 2D MOF-5. A series of test results revealed that 2-MI can exist in the crystal structure of MOF-5 nanosheets by coordination or adsorption. In addition, the presence of more exposed catalytically active sites and of weak basic sites (–NH) in MOF-5 nanosheets is beneficial for enhancing their catalytic performance in Knoevenagel condensation.